FATHER'S INVOLVEMENT IN LEARNING FROM HOME PROGRAM DURING COVID-19 PANDEMIC (Jurusan PGPAUD FIP UNNES, 2022)
This study aims to find out the level of Father's involvement in learning from home program during covid-19 pandemic in Purwosari village. The approach in this study used a mixture method of sequential explantation with the type of survey research. The subject in this study was father who had kindergarten children in Purwosari Village. Sampling technique was a census technique using the entire population of 85 fathers in 1 village in Purwosari Village, Patebon District, Kendal Regency. Data collection techniques were conducted with questionnaires, interviews and documentation. Quantitative data was analyzed using descriptive analysis of percentages and scores, while qualitative data were analyzed using the Miles and Hubermans model. The results of this study showed the level of father’s involvement in the home learning program amid covid-19 in Purwosari Village was a low category with a percentage of 53% and an average score of 2.49. With the results on each aspect can be described as follows, in Paternal Aspects Engagement had an average value of 2.67 which was in the medium category, the Paternal Accessibility aspect had an average value of 2.53 which was in the medium category, and the Paternal Responsibility aspect had an average value of 2.27 which was in the low category. The conclusion in this study was that the father basically had an understanding and awareness about the involvement in the home learning program, but in practice the father had not been able to fully present in accompanying the child in the home learning program. In addition, in the Paternal Responsibility aspect got the lowest result of 2.27 so that the father needs to be fully present in accompanying the child in the home learning program.